How do inputs and weather drive wheat yield volatility? The example of Germany. (July 2017) - Albers, Hakon; Gornott, Christoph; Hüttel, Silke
Highlights: Decomposes wheat yield volatility in input- and weather-driven categories. Rich data set with inputs, weather and phenology. Relating yield and weather offers valid approximations for climate impact research. Abstract: Increases in cereals production risk are commonly related to increases in weather risk. We analyze weather-induced changes in wheat yield volatility as a systemic weather risk in Germany. We disentangle, however, the relative impacts of inputs and weather on regional yield volatility. For this purpose we augment a production function with phenologically aggregated weather variables. Increasing volatility can be traced back to weather changes only in some regions. On average, inputs explain 49% of the total actual wheat yield volatility, while weather explains 43%. Models with only weather variables deliver biased but reasonable approximations for climate impact research.